Analisi Kesesuaian Pemanfaatan Ruang di Kelurahan Sentani Kota Distrik Sentani - Ricky Agrah Valentin Lamia; James Modouw; Juliani Wairata (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Sentani Kota Village as a strategic area experiences significant pressure due to population growth and economic activities, facing complex problems including the conversion of agricultural land and forests into residential and commercial areas, low public awareness about sustainable spatial planning, and weaknesses in law enforcement and supervision. This condition potentially threatens the environmental sustainability and ecosystem of Lake Sentani. This study aims to evaluate the suitability of spatial utilization in Sentani Kota Village, Sentani District, Jayapura Regency, focusing on two main issues: the level of conformity between existing spatial utilization and the Regional Spatial Plan (RTRW) guidelines, and the factors that support and hinder the effectiveness of RTRW implementation. Conducting overlay analysis of existing conditions and spatial pattern maps, complemented by field verification at 28 observation points and stakeholder interviews with the Spatial Planning Agency. The results show that 76.5% (2,759.07 hectares) of spatial utilization conforms to RTRW guidelines, while 22.9% (825.98 hectares) remains non-conforming, and 0.6% (21.66 hectares) violates regulations. Supporting factors include routine monitoring protocols, high conformity levels in designated areas, firm enforcement actions, and community leadership involvement. Conversely, hindering factors encompass low public compliance, non-conforming zones prone to violations, inconsistent enforcement responses, various types of violations, limited sanction mechanisms, and inadequate preventive measures. This study recommends targeted enforcement in critical zones, transition planning for non-conforming areas, lake buffer zone management, enhanced community participation, and systematic monitoring protocols to achieve more effective spatial utilization control.